Eksplorasi Efektivitas Metode Pembelajaran Interaktif Dalam Meningkatkan Minat Dan Prestasi Belajar Matematika Pada Siswa SMK 7 Makassar - Syamsir Adam; Nurasia Natsir (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
This research focuses on exploring the effectiveness of interactive learning methods in increasing interest and achievement in learning mathematics in students at SMK 7 Makassar. Through qualitative and quantitative approaches, this research investigates how the application of interactive learning methods can influence increasing student interest and achievement in mathematics subjects. The research results showed a significant increase in students' interest and achievement in learning mathematics after implementing interactive learning methods. This method helps students understand mathematical concepts better, increases their participation in the learning process, and motivates them to learn more about mathematics. This research concludes that interactive learning methods are effective in increasing students' interest and achievement in learning mathematics and should be applied more widely in mathematics education in Indonesia.